2019
DOI: 10.1292/jvms.18-0065
|View full text |Cite
|
Sign up to set email alerts
|

Memory immune responses and protection of chickens against a nephropathogenic infectious bronchitis virus strain by combining live heterologous and inactivated homologous vaccines

Abstract: In this study, we evaluated antibody and cell-mediated immune (CMI) responses in the mucosal and systemic compartments and protection against challenge with a nephropathogenic Brazilian (BR-I) strain of infectious bronchitis virus (IBV) in chickens submitted to a vaccination regime comprising a priming dose of heterologous live attenuated Massachusetts vaccine followed by a booster dose of an experimental homologous inactivated vaccine two weeks later. This immunization protocol elicited significant increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 35 publications
(67 reference statements)
1
18
0
Order By: Relevance
“…It has been shown that the vaccination strategies that use live attenuated plus inactivated vaccines induce 90% or more protection when compared to the use of live attenuated vaccines alone [30][31][32]. Further, effective protection against nephropathogenic BR-I IBV was achieved by antibody-and cell-mediated immune response induced by the combination of a live attenuated vaccine of the Mass serotype and an inactivated vaccine that has the BR-I IBV strain [33]. It is not known if host responses, particularly mucosal immune responses generated by these different vaccination strategies, are different in laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the vaccination strategies that use live attenuated plus inactivated vaccines induce 90% or more protection when compared to the use of live attenuated vaccines alone [30][31][32]. Further, effective protection against nephropathogenic BR-I IBV was achieved by antibody-and cell-mediated immune response induced by the combination of a live attenuated vaccine of the Mass serotype and an inactivated vaccine that has the BR-I IBV strain [33]. It is not known if host responses, particularly mucosal immune responses generated by these different vaccination strategies, are different in laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of live and inactivated IBV vaccines based on different genotype strains are widely used worldwide, IB outbreaks continue to occur sporadically due to high mutation rate and poor cross-protective effects of the different IBV strains (Cook et al 2001;Liu et al 2009b;Xue et al 2012;dos Santos et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More so, IBV-CS vaccine an inactivated IBV vaccine encapsulated in chitosan nanoparticles induced production of IFN-γ, IgA and IgY against IBV [88] and this is unlike the conventional inactivated vaccine, which only elicits limited mucosal immune responses. A combination of live attenuated vaccine and inactivated vaccine containing a BR-I IBV strain confer effective immune protection against infectious IBV strain through the induction of IgY anti-IBV antibodies and effector TCD8 cells and granzyme A [89]. It is believed that the induced anti-IBV IgY was as a result of the development of memory B lymphocytes after administration of live attenuated vaccine a day before re-vaccination with the oil adjuvanted inactivated vaccine, which upregulated IgY gene expression [89].…”
Section: Vaccine-mediated Immunity Against Ib and Nd 231 Vaccine-mmentioning
confidence: 99%
“…A combination of live attenuated vaccine and inactivated vaccine containing a BR-I IBV strain confer effective immune protection against infectious IBV strain through the induction of IgY anti-IBV antibodies and effector TCD8 cells and granzyme A [89]. It is believed that the induced anti-IBV IgY was as a result of the development of memory B lymphocytes after administration of live attenuated vaccine a day before re-vaccination with the oil adjuvanted inactivated vaccine, which upregulated IgY gene expression [89]. Full dose vaccination with H120 a live attenuated vaccine on a day-old chick showed full protection against IBV marked with high levels of IBV-specific IgY, IgA and cell-mediated immune genes including, IFN-γ, CD8+ T cells, and granzyme homolog A [82].…”
Section: Vaccine-mediated Immunity Against Ib and Nd 231 Vaccine-mmentioning
confidence: 99%